Public awareness and performance assessment of communal grease traps in Klang Valley, Malaysia - Arumugam, Theban; Ravindran, Priyadarshini; Sobri, Shafreeza; Ali, Salmiaton; Abdul Razak, Mus’Ab (Universiti Putra Malaysia Press, 2025)
The presence of fat, oil and grease (FOG) in wastewater has become an alarming concern worldwide, and Malaysia is no exception. FOG that escapes into the sewer system can cause sewer network blockages and overflow, contamination of water bodies and inefficient sewerage treatment plant processes, which will harm the ecosystem. This paper aims to investigate the level of awareness and current practices on FOG management among food operators and management staff in selected hotels and shopping malls in Klang Valley, Malaysia. Analysis revealed that most respondents (81.2%) had perceived awareness of FOG, and 76.2% were aware of FOG management and practices on their premises. Although awareness levels for both management and operators are high, in reality, they have not been translated into practice. This is evident from investigating the effectiveness of the existing communal grease trap design by analyzing the effluent samples. The highest levels of biochemical oxygen demand (BOD) for hotel and shopping mall effluents were 9000 mg/L and 13000 mg/L, respectively, while chemical oxygen demand (COD) values in the effluent range from 30000 to 93000 mg/L. The oil and grease (O&G) and total suspended solids (TSS) values in the effluent were in the range of 50000-85000 mg/L and 10,000-72,000 mg/L, respectively. All tested parameters were well above the permissible limit based on Malaysia’s Water Services Industry (Prohibited Effluent) Regulations 2021 (Regulation 4). This concludes that the communal grease traps investigated in this study are ineffective and most likely allow non-permissible effluent into the environment.